Larval growth and allometry in the cabbage butterfly Pieris brassicae (Lepidoptera: Pieridae). (21st November 2019) - Springolo, Arianna; Rigato, Emanuele; Fusco, Giuseppe
Abstract: By adopting a longitudinal study design and through geometric morphometrics methods, we investigated individual and ontogenetic variation in size, shape and timing during larval development of the cabbage butterfly Pieris brassicae under laboratory conditions. We found that ontogenetic size progression departs modestly, but significantly, from growth at a constant rate and that size at hatching contributes considerably to determine the size of the individual at all subsequent stages. As for the shape, ontogenetic allometry is much more conspicuous than static allometry, the latter in many cases being close to isometry. Analysis of developmental timing revealed a stage of apparently more effective developmental control at stage 3, supported by both the relatively small variance in cumulative developmental time up to stage 3 and by the pattern of correlation between duration of single stages. While presenting detailed quantitative aspects of growth in P. brassicae, in particular with respect to individual variation, this study and the associated dataset can provide a basis for further explorations of the post‐embryonic development in this insect and contribute to the ongoing investigations on growth regulation and control in insects.